Switch in codon bias and increased rates of amino acid substitution in the Drosophila saltans species group. - Rodríguez-Trelles, F (1999)
We investigated the nucleotide composition of five genes, Xdh, Adh, Sod, Per, and 28SrRNA, in nine species of Drosophila (subgenus Sophophora) and one of Scaptodrosophila. The six species of the Drosophila saltans group markedly differ from the others in GC content and codon use bias. The GC content in the third codon position, and to a lesser extent in the first position and the introns, is higher in the D. melanogaster and D. obscura groups than in the D. saltans group (in Scaptodrosophila it is intermediate but closer to the melanogaster and obscura species). Differences are greater for Xdh than for Adh, Sod, Per, and 28SrRNA, which are functionally more constrained. We infer that rapid evolution of GC content in the saltans lineage is largely due to a shift in mutation pressure, which may have been associated with diminished natural selection due to smaller effective population numbers rather than reduced recombination rates. The rate of GC content evolution impacts the rate of protein evolution and may distort phylogenetic inferences. Previous observations suggesting that GC content evolution is very limited in Drosophila may have been distorted due to the restricted number of genes and species (mostly D. melanogaster) investigated.